Influence of Transcranial Direct Current Stimulation to the Cerebellum on Standing Posture Control - Inukai, Yasuto; Saito, Kei; Sasaki, Ryoki; Kotan, Shinichi; Nakagawa, Masaki; Onishi, Hideaki (Frontiers in Human Neuroscience, 2016)
Damage to the vestibular cerebellum results in dysfunctional standing posture control. Patients with cerebellum dysfunction have a larger sway in the center of gravity while standing compared with healthy subjects. Transcranial direct current stimulation (tDCS) is a noninvasive technique for selectively exciting or inhibiting specific neural structures with potential applications in functional assessment and treatment of neural disorders. However, the specific stimulation parameters for influencing postural control have not been assessed. In this study, we investigated the influence of tDCS when applied over the cerebellum on standing posture control. Sixteen healthy subjects received tDCS (20 min, 2 mA) over the scalp 2 cm below the inion. In experiment 1, all 16 subjects received tDCS under three stimulus conditions, Sham, Cathodal, and Anodal, in a random order with the second electrode placed on the forehead. In experiment 2, five subjects received cathodal stimulation only with the second electrode placed over the right buccinator muscle. Center of gravity sway was measured twice for 60 s before and after tDCS in a standing posture with eyes open and legs closed, and average total locus length, locus length per second, rectangular area, and enveloped area were calculated. In experiment 1, total locus length and locus length per second decreased significantly after cathodal stimulation but not after anodal or sham stimulation, while no tDCS condition influenced rectangular or enveloped areas. In experiment 2, cathodal tDCS again significantly reduced total locus length and locus length per second but not rectangular and enveloped areas. The effects of tDCS on postural control are polarity-dependent, likely reflecting the selective excitation or inhibition of cerebellar Purkinje cells. Cathodal tDCS to the cerebellum of healthy subjects can alter body sway (velocity).